“Having Cleared and Embellished the Earth”: Agricultural Science and Poetic Tradition in Oliver Goldsmith’s The Rising Village - Mason, Travis V. (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
Critics have long noted a discrepancy between Canadian landscape and the imported European literary forms early Canadian writers used to describe a young country. Yet, in the early nineteenth century, some parts of the landscape were actively transformed in ways that would seemingly preclude the need for poets to transform their literary inheritance. This essay examines agricultural reform initiatives in Nova Scotia, which included deforestation in the interest of warming the temperature, as espoused in letters published in the Acadian Recorder. Focusing on Oliver Goldsmith’s The Rising Village, the essay locates a poetics at once beholden to English literary tradition and celebratory of indigenous flora and fauna's "native exoticism," both of which embrace a transformation of British North America into some place familiar to settler-colonials. Although the paradigmatic reading of early Canadian literature as struggling to fit English literary forms to a new landscape remains accurate, this reading of The Rising Village demonstrates how that paradigm struggled to gain acceptance.